Employment outcomes in family supporters of patients with early stage breast cancer and their association with patients' health‐related quality of life and financial burden. (3rd February 2022) - Veenstra, Christine M.; Braun, Thomas M.; Abrahamse, Paul H.; Wittmann, Daniela; Hawley, Sarah T.
Abstract: Background: Little is known about how cancer impacts the employment status of patients' family supporters, or about associations between patients' health‐related quality of life, perceived financial burden, and supporters' employment trajectory. Methods: We surveyed patients with early stage breast cancer reported to the Georgia and Los Angeles SEER registries in 2014–15, and their spouse/partner or other family supporters. Patients and supporters were asked about employment impacts of the patient's cancer, and descriptive analyses of supporters' employment trajectories were generated. We measured patients' health‐related quality of life (HRQoL) using the PROMIS scale for global health. We measured patients' perceived financial burden attributed to cancer by asking them two questions regarding (i) their financial status since their breast cancer diagnosis and (ii) how much it was impacted by their breast cancer and treatment. Associations between patients' HRQoL, perceived financial burden, and supporters' employment status were assessed using linear mixed model regression analyses. Results: In total, 2502 patients (68% response rate) and 1203 supporters (70% response rate) responded; 1057 paired patient‐supporter dyads were included. Similar proportions of spouse/partner and other family supporters reported missed work and lost employment due to patients' cancer. After adjustment, lower HRQoL and an increased odds of perceived financial burden among patients were associated with changes in other family supporters' employment (both p  < 0.05), but not with changes in spouses'/partners' employment. Lower HRQoL was also associated with changes in patients' own employment among patients with both types of supporters (both p  < 0.001). An increased odds of perceived financial burden among patients was associated with changes in patients' employment only in those supported by other family members ( p  < 0.001). Conclusions: Both spouse/partner and other family supporters faced adverse employment outcomes due to patients' cancer. This contributes to worse HRQoL and greater perception of financial burden among patients, especially those whose supporter is not a spouse/partner. Abstract : We performed a large, population‐based survey study of diverse patients with early stage breast cancer and their spouses, partners, and other family supporters to understand how cancer impacts the employment status of patients' spouse/partner and other family supporters, and about associations between patients' health‐related quality of life, perceived financial burden, and their supporters' employment trajectory. Both spouse/partner and other family supporters faced adverse employment outcomes due to patients' cancer. This contributed to worse health‐related quality of life and greater perception of financial burden among patients, especially those whose supporter is not a spouse/partner.